English as a School Subject: A Historical Analysis of English Curriculum Standards in Taiwan - Ke, I-Chung (English teaching & learning, 2024)
Curriculum is not only a product of political and sociocultural negotiation but also a projection of the imaginary of an ideal society because it aims to educate students into citizens in an imaginary future world. The global spread of English in the past century has greatly impacted the curriculum in non-English-speaking countries. This study examines the roles of English in the curriculum imaginaries using a historical analysis of English curriculum standards and documents in Taiwan. Findings show that the roles of English in the curriculum have changed from a foreign elite language to an international, scientific, and communicative medium for global sustainable development. The evolvement of English in the curriculum suggests a trend of incorporating English as basic literacy as secondary schools gradually changed from elite to mass education. However, changes in the curriculum imaginaries have not been reflected in the total required weekly teaching hours of English in high school, junior high school, and elementary schools under different curriculum standards. Adjustments in policies are needed to bring the imaginaries closer to reality.